2009
DOI: 10.4049/jimmunol.0804166
|View full text |Cite
|
Sign up to set email alerts
|

Coexpression of IL-18 Strongly Attenuates IL-12-Induced Systemic Toxicity through a Rapid Induction of IL-10 without Affecting its Antitumor Capacity

Abstract: IL-12 is an excellent candidate for the treatment of cancer due to its ability to drive strong antitumor responses. Recombinant IL-12 protein is currently used in cancer patients; however, systemic expression of rIL-12 presents disadvantages including cost and dose limitation due to its toxicity. In this study, we used hydrodynamic shear of cDNA as a tool to achieve systemic expression of IL-12. We found that sustained but toxic levels of serum IL-12 could be generated in 6- to 7-wk-old B6 mice after a single … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
44
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(53 citation statements)
references
References 46 publications
9
44
0
Order By: Relevance
“…ALT levels, which are often elevated following systemic IL-12 administration, 49 were substantially increased in mice receiving daily i. p. IL-12 but not a single i.t. chitosan/IL-12 injection.…”
Section: Discussionmentioning
confidence: 97%
“…ALT levels, which are often elevated following systemic IL-12 administration, 49 were substantially increased in mice receiving daily i. p. IL-12 but not a single i.t. chitosan/IL-12 injection.…”
Section: Discussionmentioning
confidence: 97%
“…Our previous work also demonstrated that IFNγ was partially responsible for the IL-12-side effects. Moreover, our data demonstrated that increased survival of IL-12+IL-18-treated mice is associated with early IL-10 production and a reduction of IFNγ and TNFα serum levels [10]. In this context, the present work demonstrates that by using hydrodynamic injection to induce systemic co-expression of IL-12+IL-18 cDNAs or by pre-injecting a low dose of IL-12 cDNA prior to a large dose of IL-12 cDNA, we observed significantly increased survival and diminished hepatotoxicity.…”
Section: Introductionmentioning
confidence: 51%
“…Moreover, co-expression of IL-12+IL-18 was able to improve survival by diminishing IL-12-side effects [10]. Our previous work also demonstrated that IFNγ was partially responsible for the IL-12-side effects.…”
Section: Introductionmentioning
confidence: 57%
See 1 more Smart Citation
“…In later studies, the possibility to improve IL-12 as a therapeutic agent was explored by co-injecting mice with IL-12 and IL-18 cDNA. Surprisingly, this resulted in the rapid induction of IL-10, neutralization of tumour recrosis factor α (TNFα) and reduction in toxicity while anti-tumour activity of IL-12 was still retained [47]. Synergism was also shown in the clinic when patients with colorectal cancer were treated with pre-operative IL-2 immunotherapy resulting in increased IL-12 activity and decreased levels of VEGF in patient sera [48].…”
Section: Angiogenesis Inhibition In Combination With Immunotherapymentioning
confidence: 98%